Careless whiskers - James, Miranda (James, Miranda. Cat in the stacks mystery ;, 2020)
"When Charlie's daughter is falsely accused of the murder of an angsty actor, he and Diesel must put their best paws forward to crack the case in this all-new installment in the New York Times bestselling series. The theater department at Athena is putting on a play by a fledgling playwright with local connections. Charlie's son-in-law, Frank Salisbury, will be calling the directorial shots, and his daughter, Laura, will be taking on the lead female role. Laura is excited to learn that there will be a guest artist, someone she knew in Hollywood, taking on a part in the production. The older male actor whose career in film has been on the wane, arrives with a small entourage in tow and proceeds to annoy everyone involved with the production. When he dies on stage, having drunk poison in a glass Laura handed to him, Laura becomes the chief suspect in his murder. Charlie and Diesel have to prove Laura's innocence and make sure the real killer does time for his crimes"--